Strengthening long-lasting insecticidal nets effectiveness monitoring using retrospective analysis of cross-sectional, population-based surveys across sub-Saharan Africa. Issue 1 (December 2018) - Janko, Mark; Churcher, Thomas; Emch, Michael; Meshnick, Steven
Abstract Bed nets averted 68% of malaria cases in Africa between 2000 and 2015. However, concerns over insecticide resistance, bed net durability and the effectiveness of long-lasting insecticidal nets (LLIN) are growing. To assess the effectiveness of LLINs of different ages and insecticides against malaria, we conducted a population-based, cross-sectional study using data from 162, 963 children younger than 5 years of age participating in 33 Demographic and Health and Malaria Indicator Surveys conducted in 21 countries between 2009 and 2016. We used Bayesian logistic regression to estimate associations between LLIN age, insecticide type, and malaria. Children sleeping under LLINs the previous night experienced 21% lower odds of malaria infection than children who did not (odds ratio [OR] 0.79; 95% Uncertainty Interval [UI] 0.76–0.82). Nets less than one year of age exhibited the strongest protective effect (OR 0.75; 95% UI 0.72–0.79), and protection weakened as net age increased. LLINs containing different insecticides exhibited similar protection (ORdeltamethrin 0.78 [0.75–0.82]; ORpermethrin 0.79 [0.75–0.83]; ORalphacypermethrin 0.85 [0.76–0.94]). Freely-available, population-based surveys can enhance and guide current entomological monitoring amid concerns of insecticide resistance and bed net durability, and be used with locally-collected data to support decisions on LLIN redistribution campaign timing which insecticide to use.